2013
DOI: 10.1159/000355307
|View full text |Cite
|
Sign up to set email alerts
|

Allergic Disorders at a Venerable Age: A Mini-Review

Abstract: This review focuses on 3 allergic disorders of persons coming up against venerable age: asthma, allergic rhinitis, and atopic dermatitis. The prevalence of allergic diseases in the elderly ranges from 5 to 10% and appears to be rising. A gradual decline in immune function, termed immunosenescence, and age-related changes in tissue structure influence the development of these disorders. Common complications are comorbidities, polypharmacy, and adverse effects of drugs. The elderly have difficulty mounting prote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
39
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(42 citation statements)
references
References 47 publications
1
39
0
2
Order By: Relevance
“…In accordance with the literature [15], our data clearly demonstrated that the frequency of sensitization to the common inhalant allergens decreased with age. A significant decline in the frequency of sensitization to the inhalant allergens was observed in patients aged between 45 and 64 y and those aged>65 y.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…In accordance with the literature [15], our data clearly demonstrated that the frequency of sensitization to the common inhalant allergens decreased with age. A significant decline in the frequency of sensitization to the inhalant allergens was observed in patients aged between 45 and 64 y and those aged>65 y.…”
Section: Discussionsupporting
confidence: 92%
“…Proliferative T-lymphocyte response was reported to be reduced [16]. Moreover, although the activity and number of B-lymphocytes are observed to decline in elderly patients, serum autoantibody levels are found to increase [15]. These changes are termed "immunosenescence," which is thought to be a result of natural genetic aging, environmental factors, and unhealthy lifestyle or habits.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Это согласуется с данными других авторов относительно возрастных особенностей астмы, связанных с уменьше-нием с возрастом легочных объемов [6] и утяжелением течения заболевания [7]. При этом повышенная кожная чувствительность к фунгальным микст-аллергенам у боль-ных обеих групп изначально была идентич-ной и сопровождалась повышенной кож-ной чувствительностью к гистамину.…”
Section: обсуждение результатов исследованияunclassified
“…При этом эффекты «иммунологического ста-рения»: скомпроментированность эпителиальных барьеров, усиление Т-хелперных реакций 2, 17 типа [6], -а также коморбидная патология и связанная с ними лекарственная терапия [7] обуславливают до-полнительные трудности в курации пожилых боль-ных с астмой и необходимость поиска новых методов терапии.…”
unclassified